Natural Communication The Obstacle-Embracing Art of Abstract Gnomonics - Zafiris, Elias (Applied Virtuality Book Series, 2021)
In Natural Communication, the author criticizes the current paradigm of specific goal orientation in the complexity sciences. His model of "natural communication" encapsulates modern theoretical concepts from mathematics and physics, in particular category theory and quantum theory. The author is convinced that only by looking to the past is it possible to establish continuity and coherence in the complexity science.